Detection of serum antibodies of avian influenza type A, Newcastle disease, avian bronchitis and laryngotracheitis in wild aquatic birds of three Andean lagoons of Ecuador - Luzuriaga, Nivia (2019)
The aim of this study was to determine the presence of serum antibodies against four respiratory pathogens (avian influenza [AI], Newcastle disease [NDV], avian infectious bronchitis [IBV] and avian infectious laryngotracheitis [ILT]) that could affect migratory aquatic and resident birds of three high Andean lagoons of Ecuador. Blood samples (n=153) were collected from birds of seven species in the Andean lagoons of Colta, Yambo and Yahuarcocha. The presence of antibodies (Ab) against IBV and ILT was detected by an indirect ELISA (ELISAi) and by the haemagglutination inhibition test (HI); and NDV and avian influenza (H5N1 and H7N3) were detected by an ELISAc and HI. Seropositivity to NDV was 3.2% (5/153), with three cases in Yahuarcocha in the Neotropical cormorant (Phalacrocorax brasilianus), one case in Colta in the Andean coot (Fulica ardesiaca) and one in Yambo in the Andean reddish duck (Oxyura ferruginea). The seropositivity against AI was 13% (20/153), mainly in the Andean reddish duck and the Southern silvery grebe (Podicceps occipitalis) in Colta, and in the yellow-billed pintail (Anas georgica), Andean coot and Andean reddish duck in Yambo. Likewise, serum Ab was found against IBV in two cormorants in Yahuarcocha. No antibodies against ILT were found.